2012
DOI: 10.5012/bkcs.2012.33.11.3701
|View full text |Cite
|
Sign up to set email alerts
|

Four-Component Preparation of Disubstituted 1,3,4-Oxadiazoles from (N-isocyanimino)triphenylphosphorane, Phenylacetylenecarboxylic Acid, Biacetyl and Primary Amines

Abstract: A simple method has been developed for four-component synthesis of disubstituted 1,3,4-oxadiazoles using (N-isocyanimino)triphenylphosphorane, a primary amine, a carboxylic acid and biacetyl in CH 2 Cl 2 by the Ugi-4CR/aza-Wittig sequence at room temperature in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…On the other hand, ketones are restricted to be cyclic 103,113−117 or electron-deficient α-halo ketones, 108,118 α-acyl(thi)oxy propanones, 98,99,107,119 and biacetyl. 100 The mechanism proposed for the Ramazani-4CR comprises the initial steps of the classic Ugi-4CR, that is, the formation of the protonated the iminium ion 44, which subsequently adds to isonitrile 1 along with the carboxylate anion to form the corresponding α-adduct 45. 120−124 The reaction continues with the aza-Wittig sequence explained before to render the functionalized oxadiazole as a mixture of enantiomers.…”
Section: Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, ketones are restricted to be cyclic 103,113−117 or electron-deficient α-halo ketones, 108,118 α-acyl(thi)oxy propanones, 98,99,107,119 and biacetyl. 100 The mechanism proposed for the Ramazani-4CR comprises the initial steps of the classic Ugi-4CR, that is, the formation of the protonated the iminium ion 44, which subsequently adds to isonitrile 1 along with the carboxylate anion to form the corresponding α-adduct 45. 120−124 The reaction continues with the aza-Wittig sequence explained before to render the functionalized oxadiazole as a mixture of enantiomers.…”
Section: Reactionsmentioning
confidence: 99%
“…The procedure is fast, high yielding, and very clean, as the only byproducts are water and TPPO. Very soon, the scope of the reaction was extended to the use of cinnamic, phenylacetylene, and peptidic , acids, while primary ,− and peptidic amines , also participate, although giving slightly lower yields. Substituted benzyldehydes, , aromatic dialdehydes, furfural, acetaldehyde, , and cinnamaldehyde , readily react as carbonyl components.…”
Section: Oxadiazole Synthesis By Four-component Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were particularly interested in the synthesis of benzimidazoles via a method suitable for large scale preparations as well as not requiring toxic starting materials and reagent. In connection with our interest in the synthesis of heterocycles [26][27][28][29][30][31][32][33][34][35], the synthesis of N-(1H-benzimidazol-2-yl) acetamide derivatives via a two-component reaction of 1,2-phenylenediamine derivatives and trichloroacetyl isocyanate, in high yields and fairly mild reaction condition, is reported herein (Scheme 1). Also, in this work, we perform a systematic computational study of electronic structure, and properties synthesized molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] On the other hand, the aza-Wittig-mediated annulation strategy has received increased attention in view of their utility in the synthesis of nitrogen-containing heterocyclic compounds. [14][15][16][17][18][19][20][21][22] We have been interested in the synthesis of fused heterocycles via aza-Wittig reaction for some time, [23][24][25][26][27][28][29] with the aim of searching for new lead compounds. In the early studies, we reported the synthesis of pyrrolo[3,2-d]-pyrimidines from 3-amino-2-carboxylpyrroles, 30 and the synthesis of pyrrolo [3,4-d]pyrimidines from 4-amino-3-carboxylpyrroles.…”
Section: Introductionmentioning
confidence: 99%